Stability of the current characteristics of dye-sensitized solar cells in the second quadrant of the current-voltage characteristics - Shiro Iwata; Shin-ichiro Shibakawa; Naoto Imawaka; Katsumi Yoshino (Energy Reports, 2018)
Photovoltaic cells in series-connected modules may operate in the second quadrant of the current-voltage characteristics via power control circuits. In the second quadrant of the current-voltage characteristics of dye-sensitized solar cells (DSSCs), the forward currents continuously flow and the operating voltage points gradually shift toward more negative voltages. These changes are attributed to the increase in the ratio of iodide to tri-iodide in the DSSC electrolyte rather than to the decomposition and/or coupling reactions of the constituent materials. In addition, these changes are reversible reactions that can be detected based on the changes in electrolyte color or current-voltage measurements.
Keywords: 330; Dye-sensitized; Electrolyte color; Modules; Performance stability